(untitled) (Journal of Human Sciences, 2024)
This research is concerned with examining one of the significant issues in the history of the medieval Arab Islamic philosophy, related to the contribution of the influential philosopher ‘Sheikh Ibn Sina’, which was considered by many critics controversial by all the means, as some of them tend to consider it the peak of the development of philosophy in Islamic civilization. While others view it as decline of the Islamic civilizational project in its Eastern phase, this research set off from a problematic hypothesis that sees in the philosophy of Ibn Sina the commencement of adoption of the Gnostic discourse in Arab-Islamic culture and the decline of rational discourse, and to achieve this goal, the Sheikh relied on employing the theory the Gnostic overflow, in which he wanted to establish a compound separation of two types ; the first is concerned with drawing a dividing line that distinguishes the supralunar world and the sublunar world. Based on this distinction, the second separation is established, the scope of which will be the world under the orbit of the moon, and its subject is the separation between the soul and the body. By completing the two separations, the way is opened for the Gnostic Sufi discourse to enter the centre of Arab-Islamic culture. It is worth mentioning that the writer of this study tends to adopt the critical analytical Approach with the aim of interrogating texts.